Diffusion Tensor Fiber Tractography for Arteriovenous Malformations: Quantitative Analyses to Evaluate the Corticospinal Tract and Optic Radiation - Okada, T.; Miki, Y.; Kikuta, K.; Mikuni, N.; Urayama, S.; Fushimi, Y.; Yamamoto, A.; Mori, N.; Fukuyama, H.; Hashimoto, N.; Togashi, K. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: We hypothesized that diffusion tensor fiber tractography would be affected by intracranial arteriovenous malformation (AVM). The purpose of the present study was to evaluate the influence of intracranial AVM on corticospinal tract and optic radiation tractography.MATERIALS AND METHODS: The subject group comprised 34 patients with untreated intracranial AVM. Hemorrhage was present in 13 patients and absent in 21 patients. Perinidal fractional anisotropy (FA) and number of voxels along the reconstructed corticospinal and optic radiation tracts were measured, and left-to-right asymmetry indices (AIs) for those values were quantified. Patients were assigned to 1 of 3 groups: tracts distant from nidus, tracts close to nidus without neurologic symptoms, and tracts close to nidus associated with neurologic symptoms. One-way analysis of variance was used to compare differences in AI between groups. Hemorrhagic and nonhemorrhagic groups were assessed separately.RESULTS: In patients without hemorrhage, AI of optic radiation volume (P < .0001), AI of perinidal FA along corticospinal tract (P = .006), and optic radiation (P = .01) differed significantly between groups. In patients associated with hemorrhage, AI of corticospinal tract volume (P = .01), AI of perinidal FA along corticospinal tract (P = .04), and optic radiation (P = .004) differed significantly between groups.CONCLUSIONS: Corticospinal tract and optic radiation tractography were visualized in patients with AVM. In patients with both hemorrhagic and nonhemorrhagic AVM, the 2 fiber tracts close to the nidus were less visualized in the affected hemisphere than those distant from the nidus. Tracts were less visualized in patients with neurologic symptoms than in asymptomatic patients.